The Contribution of Family Environment and Learning Motivation Toward Students 'Learning Outcomes in Online Learning - Rahmadian, Rahmadian; Maksum, Hasan (Journal of Education Technology, 2020)
This study aims to measure the contribution of the family environment and learning motivation on students' learning outcomes in class XI ICT subjects. This type of research is quantitative through a correlational approach. The population of this research was all students of class XI which consisted of 4 classes with a total of 101 students. Sampling in this study was carried out by proportional random sampling with the Slovin formula of 81 respondents. The data collection instrument used a questionnaire using a Likert scale, data analysis techniques including simple regression and multiple regression. The results showed that (1) the family environment contributed to learning outcomes by 34.2%; (2) Motivation to learn contributes to learning outcomes by 33.6% and (3) Family environment and learning motivation together contribute to learning outcomes by 44.3%. Thus, the family environment and learning motivation contribute together to student learning outcomes in ICT subjects.